Research on Injection-Production Capability and Seepage Characteristics of Multi-Cycle Operation of Underground Gas Storage in Gas Field—Case Study of the Wen 23 Gas Storage - Jie Zhang; Feifei Fang; Wei Lin; Shusheng Gao; Yalong Li; Qi Li; Yi Yang (Energies, 2020)
With the increasing energy demands of current modern society, underground gas storage (UGS) in gas fields is the most popular type of UGS used to meet the seasonal variation of gas consumption. However, compared with gas fields, UGS in gas fields has the characteristics of periodic high-speed injection and production of exploitation modes and operation rules, which causes the rules of gas-water seepage and utilization of reserves to be more particular and complicated. In this paper, based on Wen 23 gas storage, the rules of multicycle injection and production flow and the utilization of UGS pore volume were investigated. The experimental results showed that variation in porosity and permeability caused by injection and production pressure changes in Wen 23 gas storage can be neglected. The pore volume of gas storage and the degree of gas recovery increased gradually in the pre-UGS gas zone, which was higher than that of reservoirs. In the initial stage of UGS operation, the pore volume of gas storage and the degree of gas recovery were low in the gas-drive-water gas zone as a result of water invasion during the process of reservoir exploitation. During operation of multicycle high-speed injection and production, the seepage conditions in the gas-drive-water gas zone gradually improved. The higher the reservoir permeability, the greater increases in pore volume and degree of gas recovery. In the gas-water transition zone, gas and water were reciprocated and displaced with the multicycle injection-production of UGS, resulting in the gradual deterioration of pore volume and gas recovery, which remained stable at a low value. The negative effects of reservoir heterogeneity on the effective utilization of UGS occurred in the gas-water transition zone. These findings may contribute to a better understanding of the rules of multicycle injection and production flow and utilization of UGS to optimize the injection-production efficiency of Wen 23 gas storage.